PERBANDINGAN KEBIJAKAN ADAM MALIK, MOCHTAR KUSUMAATMADJA DAN ALI ALATAS TERHADAP POLITIK LUAR NEGERI BEBAS AKTIF INDONESIA PADA MASA ORDE BARU - Fiky Arista; Andi Suwirta; Farida Sarimaya (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2017)
This article entitled "The Comparison of Adam Malik, Mochtar Kusumaatmadja and Ali Alatas Policies Against Independent-Active Foreign Policy In Indonesia During The New Order". The writing is motivated by the author interest to determine the policies taken by the New Order government in maintaining a free and active foreign policy taken by Adam Malik, Mochtar Kusumaatmadja, and Ali Alatas. The main issues in this research is how is the Comparison of Adam Malik, Mochtar Kusumaatmadja And Ali Alatas Policies Against Independent-Active Foreign Policy In Indonesia During The New Order? The method used in the study is the historical method consists of four phases, which are; heuristic, criticism, interpretation and historiography. In reviewing the research question, the author uses an interdisciplinary approach by using some of the concepts from political science. Based on the research, authors knew that Adam Malik, Mochtar Kusumaatmadja, and Ali Alatas had different educational backgrounds so when they are assuming his post as Foreign Minister also can be different. The difference can be seen from their focus in taking a foreign policy. Adam Malik, who is still in transition from the Old Order to the New Order, his focus was to solve the problems that occurred in the previous government. Mochtar Kusumaatmadja focuses on Archipelago and international law. Ali Alatas focuses on human rights issues and to make Indonesia as Chairman of NAM. In addition, The Three Minister of Foreign Affairs through his policy also makes Indonesia active in solving regional and international issues, as well as the Non-Aligned Organizations.